Online Mind Mapping and Brainstorming

Create your own awesome maps

Online Mind Mapping and Brainstorming

Even on the go

with our free apps for iPhone, iPad and Android

Get Started

Already have an account? Log In

Chapter 3:Multi-step Equations and Inequalities by Mind Map: Chapter 3:Multi-step Equations and Inequalities
0.0 stars - reviews range from 0 to 5

Chapter 3:Multi-step Equations and Inequalities

3.1

Words you should know

Vocaburaly Verbal Model:An expression that describes a problem using words as labels and using math sybols to relate the words Equation:A mathematical sentence formed by placing an equal sign,=,between two expressions Inverse operations: Two operations that undo each other

Example 1:Using Subtraction and Division to Solve

Solving Two-Step Equations Example 1:Using Subtraction and Division to Solve First write normal eqautions: 3x+7= -5 Subtract 7 from each side because it is a constant number: 3x+7-7= -5-7 Then simplify: 3x= -12 Divide eachside by 3: 3x/3=-12/3 Simplify again and you get the answer: x= -4 To check your answer do the following Write the normal equations: 3x+7=-5 Substitute -4 instead of x, if you get the good answer bravo: 3(-4)+7?=-5 Check the solutions: -5=-5

Example 2: Using Addition and Multiplication to Solve

Example 2: Using Addition and Multiplication to Solve Write original equation:x/2-3=1 Add 3 to each side :x/2-3+3=1+3 Simplify:x/2=4 Multiply each side by 2:2(x/2)=2(4) Simplify=8 To check your answer do the following Check: Write original equation:x/2-3=1 Substitute 8 for x:8/2-3?=1 Solution checks:1=1

Example 3: Combining like terms after

Examaple 3 Write original equation:7-4y+=9 Subtract 7 from each side:7-4y-7=19-7 Simplify:-4y+12 Divide each side by 4:-4y/-4=12/-4 Simplify:y=-3 To check do the following: Write original equation:7-4y+=9 Substitute -3 for y:7-4(-3)?=19 Solution checks:19=19

3.2

Solving Equations Having Like Terms and Parentheses EXAMPLE 1:WRITING AND SOLVING AN EQUATION Subsitute:5.20n+0.80n+47=377 Combine like terms:6.00+47=377 Subract 47 from each side:6n+47-47=377-47 Simplify:6n=330 Divide each side by 6:6n/6=330/6 Simplify:n=55 EXAMPLE 2:Solving Equations Using The Distributive Property

EXAMPLE 1:WRITING AND SOLVING AN EQUATION

EXAMPLE 1:WRITING AND SOLVING AN EQUATION Substitute:5.20n+0.80n+47=377 Combine like terms:6.00+47=377 Subtract 47 from each side:6n+47-47=377-47 Simplify:6n=330 Divide each side by 6:6n/6=330/6 Simplify:n=55

EXAMPLE 2:Solving Equations Using The Distributive Property

Example 2   Write original equation:-21=7(3-x) Distributive property:-21=-21-7x Subtract 21 from each side:-21-21=21-7x-21 Simplify:-42=-7x Divide each side by -7:-42/-7=-7x/-7 Simplify:6=x  

3.3

Solving an equation with variables on both sides

EXAMPLE 1   Write original equation:7n-5=10n+13 Subtract 7n from each side:7n-5-7n=10n+13-7n Simplify:-5=3n+13 Subract 13 from each side:-5-13=3n+13-13 Simplify:-18=3n Divivde each side by 3:18/3=3n/3 Simplify:-6=n  

Writing and solving equation

Example 2   Substitute:10s=5s+60 Subtract 5s from each side:10s-5s=5s-5s+60 Simplify:5s=60 Divide each side by 6:5s/5=60/5 Simplify:s=12  

3.5

   

Example 1 Solving inequality using division

Example 1 Original Inequality:-10t > 34 Divide each side by -10 .Reverse inequality symbol:-10t/-10 < 34/-10 Simplify:t

Example 2 Solving an inequality using division

Example 2   Original Inequality:m/-3 >3 Multiply each side by -3 .Reverse inequality symbol:-3 times m/-3 < -3 times 3 Simplify:m

Vocabulary

INEQUALITY: is a statement formed by placing an inequality symbol between two expressions. SOLUTION OF AN INEQUALITY: The sets  of all numbers that produce true statements when substituted for thr variable in the inequality EQUIVALENT INEQUALITIES: are inequalities that have the same solution

3.6

Example 1 Writing and Solving a multi Step Inequality

Example 1 Substitute: 88+10g > 138 Subtract 88 from each side:88+10g-88 > 138-88 Simplify:10g >50 Divide each side by 10: 10g/10 >50/10 Simplify:g > 5

Example 2: Solving a Multistep Inequality

Example 2   Original inequality:x/-4-6 > -5 Add 6 to each to side:x/-4-6+6 > -5+6 Simplify:x/-4> 1 Multiply each side by -4. Reverse inequality symbol.: -4xX/-4 < -4x1 Simplify: x < -4